Combined effect of nano-silica, super absorbent polymers, and synthetic fibres on plastic shrinkage cracking in concrete. (20th December 2018) - Olivier, Gerhard; Combrinck, Riaan; Kayondo, Muzafalu; Boshoff, William P.
Highlights: Inclusion of nano-silica in concrete accelerates plastic shrinkage cracking. Nano-silica reduces the drying time of plastic concrete. Super absorbent polymers reduce plastic shrinkage cracking in nano-silica mixes. Fibres and super absorbent polymers when combined are not effective. Abstract: This research attempts to further add onto the existing knowledge-base of the utilisation of nano-silica in concrete by understanding its influence on plastic shrinkage in concrete, a subject with hardly any specific literature available. The results of extensive experimentation reveal that the adoption of nano-silica in concrete mixes should be cautiously undertaken, as it behaves in such a way to cause acceleration of the mechanisms of plastic shrinkage. This research has further been done in tandem with the combined plastic shrinkage crack mitigation methods, such as the use of synthetic fibres and super absorbent polymers (SAP) in concrete. The combined use of nano silica with SAP can be effective in alleviating the associated plastic shrinkage cracking. Synthetic micro-fibres too are useful in lessening plastic shrinkage cracking in nano silica mixes, but are not as effective as SAP. The mechanism of acceleration of plastic shrinkage cracking by nano silica is attributed to the finer particles of the material, causing reduced bleeding amounts in mixes in which it is incorporated.